Weight watchers ultimate chicken cookbook : more than 250 fresh, fabulous recipes for every day (St. Martin's Griffin, 2013)
"Everyone loves chicken--it's delicious, versatile, economical, and perfect for everything from quick weekday dinners to leisurely weekend meals. It's also a go-to ingredient for anyone trying to lose weight. These chicken recipes are loved by Weight Watchers members and anyone interested in cooking (and eating) delicious, satisfying dishes. The best are all here, in easy-to-use categories, including: Tasty small bites, from Chicken Skewers with Spicy Peanut Dipping Sauce to Chicken and Cheddar Quesadillas Salads, both classic and thoroughly modern, like Chicken, Mango, and Black Bean Salad or Grilled Chicken Sausage with Roasted Potato Salad Tempting soups and stews, such as Mexicali Chicken Soup with Lime and Chicken Stew with Dumplings Company favorites, including Hunter-Style Chicken and Chicken, Shrimp, and Kielbasa Paella Something from the oven, such as Chicken Baked in Salt Crust and Green-Olive Roast Chicken Grilled main dishes, like Chicken Under a Brick and Tequila-Citrus Chicken Slow-cooker favorites including Chicken and Ham Cassoulet and Meatballs in Cinnamon-Tomato Sauce Dishes ready in 20 minutes, like Chicken and Edamame Stir-Fry and Chicken Caesar Pitas Each of the 250 recipes includes complete nutritional information, as well as Weight Watchers PointsPlusʼ values adhering to the new Weight Watchers 360ʻ program. Also highlighted are countless substitution suggestions, cooking and portioning tips, and much, much more"--